Making Women's Voices Count : Integrating Gender Issues in Disaster Risk Management - Overview and Resources for Guidance Notes - World Bank (World Bank, Washington, DC, 2017)
The countries of East Asia and the Pacific (EAP) are among the most vulnerable in the world to the physical, social, and economic effects of natural disasters. Disaster impacts are not distributed uniformly within a population. Due to existing socio-economic conditions, cultural beliefs and traditional practices, women and men are affected differently. In many cases, the mortality rates for women in the aftermath of a disaster are much higher than those of men. For example, women represented an estimated 61 percent of fatalities in Myanmar after Cyclone Nargis in 2008, 70 percent after the 2004 Indian Ocean Tsunami in Banda Aceh, and 91 percent after Cyclone Gorky in Bangladesh in 1991. Failure to consider the different impact disaster have on women and men are likely to lead to overlooking the true costs of disasters and making disaster risk management (DRM) support less effective. Gender-blind responses can also reinforce, perpetuate and increase existing gender inequalities, making bad situations worse for women and other vulnerable groups. To make DRM effective, therefore, it is essential that both women and men's voices and needs are integrated on equal terms men in the design and implementation of DRM programs. To address key issues and bottlenecks for mainstreaming gender issues into disaster risk management projects; and to help teams design and implement gender dimensions into disaster risk management work, the infrastructure and social development groups of the World Bank's Sustainable Development Department in the East Asia and Pacific region have jointly produced a set of operationally relevant guidance notes for World Bank staff, clients and development partners. Grounded in extensive field work in Lao PDR and Vietnam, and drawing on the significant amount of material already available, these notes aim to condense a number of complex issues and themes to provide 'first stop' practical information.